2021
DOI: 10.1155/2021/6702965
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Efficacy and Safety of Recombinant Human Prourokinase and Alteplase in the Treatment of STEMI and Analysis of Influencing Factors of Efficacy

Abstract: Objective. To compare the efficacy and safety of recombinant human prourokinase (rhPro-UK) and alteplase for thrombolytic therapy in acute ST-segment elevation myocardial infarction (STEMI) and to analyze the related factors affecting efficacy. Methods. From January 2017 to December 2019, 100 patients diagnosed with STEMI were selected and randomly divided into the control group (n = 50) and the observation group (n = 50). Based on conventional treatments, the control group was treated with alteplase, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…15 Previous research found that prourokinase, as a novel and fibrin-specific anticoagulant, not only effectively recanalized blood vessels and improve the cardiac function of patients with STEMI, but also had very low rate of bleeding complications, which may provide an alternative and appropriate thrombolytic drug option for STEMI patients. 19,20 Besides, this study showed that patients receiving thrombolysis alone had worse in-hospital ischemic outcomes. Previous studies have shown that plaque rupture and plaque erosion are the 2 most common underlying mechanisms for sudden cardiac death and acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…15 Previous research found that prourokinase, as a novel and fibrin-specific anticoagulant, not only effectively recanalized blood vessels and improve the cardiac function of patients with STEMI, but also had very low rate of bleeding complications, which may provide an alternative and appropriate thrombolytic drug option for STEMI patients. 19,20 Besides, this study showed that patients receiving thrombolysis alone had worse in-hospital ischemic outcomes. Previous studies have shown that plaque rupture and plaque erosion are the 2 most common underlying mechanisms for sudden cardiac death and acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 71%
“…15 Previous research found that prourokinase, as a novel and fibrin-specific anticoagulant, not only effectively recanalized blood vessels and improve the cardiac function of patients with STEMI, but also had very low rate of bleeding complications, which may provide an alternative and appropriate thrombolytic drug option for STEMI patients. 19, 20…”
Section: Discussionmentioning
confidence: 99%
“…U is the flow velocity in the clot, which is calculated from Darcy’s law: where k is the permeability of the clot in unit . It is calculated from the Davis equation, and further details can be found in Piebalgs et al [ 18 ]. is the dynamic visocity in unit , and is the pressure drop per unit length of the clot.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, none of these tPA variants has shown better functional clinical outcomes than alteplase for AIS treatment so far [ 11 , 14 ]. Recent clinical research from developing countries found that IV urokinase and its precursor, pro-urokinase, seem to have similar efficacy and safety to alteplase in treating mild to moderate AIS, while the cost of urokinase is only one-tenth of that of alteplase [ 15 , 16 , 17 , 18 , 19 , 20 ]. These contested clinical results did not fully reflect the theoretical advantage of drugs as scientists expected.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant human prourokinase (Pro-UK) is a fibrin-specific plasminogen activator that shares structural similarities with tissue plasminogen activator but functions via a different mechanism ( 8 ). Studies show that Pro-UK presents with fewer hemorrhagic complications and lower re-occlusion rate in patients with acute STEMI compared with conventional drugs ( 9 , 10 ). In addition, certain prospective study found that Pro-UK decreases MACEs whereas a retrospective study revealed that Pro-UK does not affect MACEs ( 11 ).…”
Section: Introductionmentioning
confidence: 99%